ASET JAMINAN ATAS NAMA PIHAK KETIGA SEBAGAI HARTA PAILIT (STUDI PUTUSAN NOMOR: 15/Pdt.SUS-GUGATAN LAIN-LAIN /2019/ PN.NIAGA .JKT.PST): Security Assets On Behalf Of Third Parties As Bankruptcy Property (Study Decision Number: 15/Pdt.Sus-Other Lawsuits/2019/PN.Niaga.Jkt.Pst) - Siagian, Nico Grevandi M; Wicaksana, Arif (Faculty of Law, Universitas Trisakti, 2024)
Bankruptcy often occurs when the list of bankruptcy assets of bankrupt debtors is added to the collateral assets of non-debtor third parties by the curator, this is done to protect the interests of creditors. This study intends to discover whether the bankruptcy estate includes the collateral assets of non-debtor third parties, as well as to see the authority of the curator to execute collateral assets owned by third parties who are not bankruptcy debtors. In this normative legal research, qualitative descriptive analysis is utilized. It was found that this research concludes that bankruptcy assets do not include debt guarantees owned by third parties Thus, there is no authority possessed by the curator in managing the debt guarantees of bankrupt debtors, which is contrary to Law Number 37 of 2004 concerning Bankruptcy & Suspension of Debt Payment Obligations, as found in Decision Number: 15/Pdt.Sus-Other Suits/2019/PN.Niaga.Jkt.Pst. Bankruptcy is a legal issue that is quite complex, so it requires caution in discussion and decision-making.